Color Doppler imaging characteristics of RPE neoplasms: A study of 17 cases - Zhou, Nan; Yang, Wenli; Wei, Wenbin (Frontiers in Ophthalmology, 2022)
Abstract Purpose: To report the Color Doppler imaging (CDI) features of 17 patients with RPE neoplasms. Design: Retrospective, observational case series. Participants: Seventeen patients with RPE adenoma/ adenocarcinoma. Methods: Contrast-Enhanced Color Doppler ultrasonography (CDU) was performed in 16 patients with RPE adenoma and 1 patient with adenocarcinoma. Result: All 17 RPE neoplasms showed well-defined margins. The oval mass was observed in eleven tumors, lenticular-shaped in four tumors, and flat in two tumors. On CDI, the RPE lesions showed homogeneous reflectivity of moderate intensity with no choroidal excavation. After Contrast-Enhanced administration of sulfur hexafluoride, mild enhancement was identified in six tumors and moderate enhancement in eleven tumors. In all 17 RPE adenomas/adenocarcinoma, Contrast-Enhanced CDU time–intensity curves (TIC) exhibited the fast fill-in and slow washout-shaped curves with dominant vessel within the RPE lesions. A “black-linear” sign (defined as low signal intensity linear zone located between tumor and enhanced choroid on CDI) was noted in all 17 patients with RPE neoplasms. Conclusions: This preliminary study noted a "black linear" sign on CDI of RPE lesions for the first time. The novel sign may be a diagnostic characteristic of RPE neoplasms and help to distinguish this rare entity from uveal melanomas.